2019
DOI: 10.1161/circresaha.118.313236
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Management in Older and Frail Older Patients

Abstract: The prevalence of arterial hypertension, particularly systolic hypertension, is constantly rising worldwide. This is mainly the clinical expression of arterial stiffening as a result of the population's aging. Chronic elevation in blood pressure represents a major risk factor not only for cardiovascular morbidity and mortality but also for cognitive decline and loss of autonomy later in life. Clinical evidence obtained in community-dwelling older people with few comorbidities and preserved autonomy supports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
218
1
43

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(267 citation statements)
references
References 136 publications
(159 reference statements)
5
218
1
43
Order By: Relevance
“…Although our results add support to considering cognitive function in clinical decision making for hypertension therapy, 31 the precise threshold at which inaction or even deprescribing should be preferred is unclear. 5 One limitation of SPRINT's design is that the presence of MCI was not adjudicated at baseline, and so we were forced to use an ad hoc categorization of cognitive status based on the MoCA. Although we categorized participants based on ageand education-specific normative data, the thresholds we used were derived from an Irish population and have not been validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our results add support to considering cognitive function in clinical decision making for hypertension therapy, 31 the precise threshold at which inaction or even deprescribing should be preferred is unclear. 5 One limitation of SPRINT's design is that the presence of MCI was not adjudicated at baseline, and so we were forced to use an ad hoc categorization of cognitive status based on the MoCA. Although we categorized participants based on ageand education-specific normative data, the thresholds we used were derived from an Irish population and have not been validated.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, hypertension treatment for adults 80 years or older is frequently complicated by multiple chronic conditions such as frailty, polypharmacy, and cognitive impairment. 4,5 Observational analyses indicate an attenuation of the association between elevated blood pressure (BP) and the incidence of vascular and nonvascular disease with increasing age, 6,7 suggesting that the balance of risk to benefit for hypertension treatment may be different for adults 80 years of age or older as compared with adults in their 60s and 70s. Several studies also suggest that older adults with robust functional status may be more likely to benefit from hypertensive therapy, with weaker or null associations between elevated SBP and adverse outcomes in adults with impaired function.…”
mentioning
confidence: 99%
“…Noticeably, low DBP increased not only 30 day but also 1 year readmission risk. A plausible explanation could be that SBP increases with age, whereas DBP remains stable or even decreases spontaneously in older adults, especially in the presence of arterial stiffness, and a declining BP may further decrease an already low DBP, which in turn leads to lower perfusion 36 . At low perfusion pressures, chronic coronary hypoperfusion occurs and associates with myocardial damage, and eventually ventricular function worsens.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in these very elderly individuals, 8 tion-based cohort of 3075 community-dwelling men and women, aged 70-79, showed that lipid profile could not efficiently predict CVD and in general poorly discriminated between persons who experienced a cardiovascular event and those who did not, underestimating the absolute CVD risk by 51% in women and 8% in men. 7 Summarizing, the present study showed that in elderly individuals 70-78 years old classic risk factors, such as lipidemic profile and blood pressure levels, were not identified as significant CVD predictors.…”
mentioning
confidence: 99%
“…These age groups are further characterized by increased variability and instability of both their cognitive and functional state, of severe frailty or maybe even full dependence. Especially in these very elderly individuals, classic risk factor such as increased BP levels or body mass index (BMI) might not only lose their importance but even have a reverse causality, confounding the estimated risk stratification. Therefore, and in order to provide better information for the estimation of CVD risk in this population, alternative approaches such as the measurement of functional arterial characteristics or endothelial dysfunction and specific treatment strategies have been suggested…”
mentioning
confidence: 99%